ANALISIS DAN DESAIN SISTEM PENJUALAN KONSINYASI MENGGUNAKAN PENDEKATAN BERORIENTASI OBJEK LIGHTWEIGHT RATIONAL UNIFIED PROCESS: ANALYSIS AND DESIGN OF CONSIGNMENT SALES SYSTEM USING AN OBJECT ORIENTED LIGHTWEIGHT RATIONAL UNIFIED PROCESS APPROACH - Mohammad Fajar; Richla Rahmatika; Afifah Afifah (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2024)
The aim of this study is to apply Lightweight Rational Unified Process (RUP) approach in modeling consignment sales information systems. Data collection is performed through literature studies, interviews and evaluation of modeling results systems. The application of the Lightweight RUP method in this research is carried out by following each stage of the approach, starting from requirements stage, analysis stage, then design stage, and the implementation stage where the connection between one stage and another can be maintained through the artifacts produced. In the requirements stage, usecase is made based on the requirements table which contains system features based on literature studies related to sales information systems and through interviews of the potential users. Furthermore, the usecase is the basis for making a number of diagrams at the analysis stage, namely activity diagrams and sequence diagrams. At the design stage, platform selection needs to be done first, so that the class diagram that will be designed to adjust to the platform chosen. In addition, at the final stage of the design, the author adds the evaluation process to the completeness of the class diagram before translated them into program code. Evaluation at the final stage of the design shows that the created class diagram has fulfilled all aspects of completeness so that it is possible to be mapped to the final target platform selected, namely the Java programming language. While the evaluation of generated program code on the Java platform shows that the cashier will able to use the desktop application to make sales transactions. As for the Android platform-based application can be used by the consignor to see the information on the status of the sold items (cakes).